Heat-pulse propagation in functionally graded thin layers. (October 2017) - Ciarletta, M.; Sellitto, A.; Tibullo, V.
Abstract: In the present paper we study how thermal pulses propagate in functionally graded thin layers. The present theoretical analysis lies on a heat-transport equation which goes beyond the classical Fourier law. The compatibility of that equation with the main tenets of continuum mechanics is investigated by means of second law of thermodynamics. Theoretical considerations are also made on the nonequilibrium temperature, the thermal-conductivity tensor and the form of the specific-entropy flux.